Analisis Biaya Kualitas Terhadap Peningkatan Laba Usaha Pada CV. Eline Anugerah Kreasi Di Surabaya - Natalia Kristina; Tjandra Wasesa; Wiratna Wiratna; Diana Zuhroh; Heri Toni (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This research is a type of research with qualitative methods with a descriptive approach. This study aims to determine the cost of quality at CV. Eline Anugerah Kreasi. The subject of this research is CV. Eline Anugerah Kreasi and the object of research is the quality cost of the company. Data analysis was carried out by analyzing quality cost reports for the last 2 years, namely: 2021 and 2022 to find out how much is spent each year related to the cost of quality in the products sold. The method used by the author is documentation, interviews with employees or managers who are directly related to quality cost reports and then analyzed descriptively, as well as records in the company which are also related to quality costs. The results showed that CV. Eline Anugerah Kreasi had not fully implemented the quality costing method, even though it looked good and had more turnover. It turned out that the profit generated did not experience a significant increase every month, this was due to the excessive spending to ensure product quality, things that should be the essence were shifted by inefficient spending. From what has been described above, a conclusion can be drawn that it is important to apply the quality cost method in a company, not only to pay attention to what is needed to improve or maintain the quality of an item, but also to pay attention to the correct application of quality costs.